Asuhan Kebidanan Komprehensif pada Ny. Y Umur 23 Tahun G1P0A0 di PMB Yohana Puspiati Mukiran Kaliwungu Laporan Continuity Of Care (COC) - Harina Noviyanti; Cahyaningrum (Universitas Ngudi Waluyo, 2025)
The neonatal and postpartum periods are critical for both mother and infant in physiological and psychological adaptation. Proper care during these periods, including neonatal monitoring, breastfeeding support, uterine involution assessment, and family planning counseling, plays an essential role in preventing complications and promoting maternal and infant health. This study aims to analyze midwifery care provided to neonates, postpartum mothers, and family planning clients, and to assess the effectiveness of midwifery interventions in supporting physiological and psychological adaptation.. This research employed a cross-sectional design with a sample of 40 respondents selected using the purposive sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square test to examine the relationship between menarche age and menopause age. This descriptive observational study was based on midwifery care records of a primiparous mother and her infant during neonatal and postpartum visits, as well as family planning counseling. Data were collected through subjective and objective assessments, including vital signs, neonatal reflexes, weight and length measurements, uterine condition, breastfeeding adequacy, and acceptance of contraception methods. Menarche age is significantly associated with menopause age. Factors such as ovarian reserve, hormonal changes, and genetic influences likely play a role in this relationship. These findings highlight the importance of early reproductive health monitoring to mitigate the risks of early menopause and its health effects. The observations showed that the neonate was in a physiological normal condition with good APGAR scores, complete primitive reflexes, appropriate growth for age, and received immunizations and vitamins according to schedule. The mother exhibited normal uterine involution, adequate breast milk production after stimulation, and no signs of infection or abnormal bleeding. Family planning counseling led to an informed decision to use an IUD effectively. Integrated midwifery care for neonates, postpartum mothers, and family planning clients supports optimal physiological and psychological adaptation, prevents complications, and enhances mothers’ understanding of self-care and infant care. Abstrak Abstrak Masa neonatal dan nifas merupakan periode kritis bagi ibu dan bayi dalam proses adaptasi fisiologis dan psikologis. Perawatan yang tepat selama periode ini, termasuk pemantauan neonatus, pemberian ASI, involusi uterus, serta konseling keluarga berencana, berperan penting dalam mencegah komplikasi dan mendukung kesehatan ibu dan bayi. Penelitian ini bertujuan untuk menganalisis asuhan kebidanan pada neonatus, nifas, dan keluarga berencana, serta menilai efektivitas intervensi kebidanan dalam mendukung adaptasi fisiologis dan psikologis ibu dan bayi. Studi ini menggunakan metode observasional deskriptif berdasarkan catatan asuhan kebidanan pada seorang ibu primipara dan bayinya selama kunjungan neonatus dan nifas, serta konseling keluarga berencana. Data dikumpulkan melalui pemeriksaan subjektif dan objektif, analisis tanda vital, refleks bayi, berat badan, panjang badan, kondisi uterus, produksi ASI, dan penerimaan metode kontrasepsi. Hasil observasi menunjukkan neonatus dalam kondisi fisiologis normal dengan skor APGAR baik, refleks primitif lengkap, pertumbuhan sesuai usia, dan menerima imunisasi serta vitamin sesuai jadwal. Ibu dalam periode nifas menunjukkan involusi uterus normal, ASI yang memadai setelah stimulasi, tanpa tanda infeksi atau perdarahan abnormal. Konseling keluarga berencana menghasilkan keputusan penggunaan KB IUD secara sadar dan tepat. Asuhan kebidanan yang terintegrasi pada neonatus, nifas, dan keluarga berencana dapat mendukung adaptasi fisiologis dan psikologis ibu serta pertumbuhan optimal bayi, mencegah komplikasi, dan meningkatkan pemahaman ibu terhadap perawatan diri dan bayi.